Tree-crop interactions : (CAB International in association with the International Centre for Research in Agroforestry, 1996)
The potential role and benefits of agroforestry in sustainable agriculture have been recognized for some time. However, until recently there has been only a limited amount of quantitative physiological evidence to support this. This book breaks new ground in showing how the principles of crop physiology can be applied to the understanding of tree-crop interactions (Syndetic solution)